Influence of Debt To Equity Ratio (DER) and Earning per Share (EPS) on Stock Price PT Nippon Indosari Corpindo Tbk - Ade Irawan Saputra (YPPP AL-AMSI, 2021)
This study aims to determine the effect of the Debt to Equity Ratio (DER) and Earning per Share (EPS) partially or simultaneously on the share price of PT. Nippon Indosari Corpindo Tbk period 2010-2020. The independent variables tested in this study are Debt to Equity Ratio (DER) as X1 and Earning per Share (EPS) as X2, while the dependent variable is Stock Price. This research method uses the associative method with a quantitative approach. The population in this study is the financial statements of PT. Nippon Indosari Corpindo Tbk and the sample used is the balance sheet and income statement for 2010-2020 which has been published on its official website, namely www.sariroti.com and www.idnfinancials.com. The results of the t-test (partial) show that DER (X1) has a negative but not significant effect on the Stock Price (Y), and EPS (X2) has a positive but not significant effect on the Stock Price (Y). The results of the F (simultaneous) test show that simultaneously Debt to Equity Ratio (X1) and Earning per Share (X2) have a positive but not significant effect on Stock Price (Y).